Investigation of preinguinal approach for removal of urachal abscess in three Japanese black cattle older than 18 months of age - SATO, Reiichiro; HAYASHI, Jun; FUKE, Naoyuki; SAITO, Eren; HIDAKA, Kanako; SAKA, Hideki; SATOH, Hiroyuki; STEINER, Adrian (Journal of Veterinary Medical Science, 2024)
This study investigated the diagnostic and surgical management of urachal abscessation involving the urinary bladder in three cattle aged >18 months. While the abdominal floor or paralumbar fossa are typically considered for accessing the urachus and bladder in calves and heifers, the distance is too great to perform the procedure under direct vision in adult cows. Therefore, a novel preinguinal approach was used for access in cows with urachal abscesses after 18 months. Access was successfully achieved in all the three cows through a preinguinal incision to the urachal abscess at the apex of the bladder. However, in cases wherein the abscess and adhesions are severe, removal may be challenging or may necessitate a combined median or paramedian approach.